1995
DOI: 10.1002/1097-0142(19950101)75:1<11::aid-cncr2820750104>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex are independent predictors of 5-fluorouracil toxicity. Analysis of a large scale phase III trial

Abstract: Background. Cancer is most common in older age groups, but little information is available with regard to the impact of age on chemotherapy toxicity. This study was undertaken to determine if age is an independent risk factor for 5‐fluorouracil (5‐FU) toxicity. Methods. Toxicity data from a prospective, randomized, multiinstitution trial of 5‐FU‐based treatment for advanced colorectal cancer were analyzed. Toxicity for each organ system was graded. Individual organ toxicity proportions were compared using chi‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
96
3
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(105 citation statements)
references
References 30 publications
2
96
3
4
Order By: Relevance
“…The current analysis also shows no difference between sexes in objective response rate or survival. The same is true for various otherwise rather divergent data about age and toxicity (Stein et al, 1995;Cascinu et al, 1996;Chiara et al, 1998;Popescu et al, 1999). Response and survival were not affected in these studies as they were in the current study, regardless of a difference in tolerance of 5-FU-based therapy between younger and older patients.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The current analysis also shows no difference between sexes in objective response rate or survival. The same is true for various otherwise rather divergent data about age and toxicity (Stein et al, 1995;Cascinu et al, 1996;Chiara et al, 1998;Popescu et al, 1999). Response and survival were not affected in these studies as they were in the current study, regardless of a difference in tolerance of 5-FU-based therapy between younger and older patients.…”
Section: Discussionsupporting
confidence: 66%
“…Apart from another small patient series with rectal cancer undergoing preoperative radiochemotherapy (Dahl et al, 1994), to our knowledge, no other conclusive data are available about treatment tolerance as a potential prognostic marker for response despite the fact that in 480% of all patients receiving chemotherapy some kind of side effects (of course largely depending on which chemotherapy regimen is administered) will occur. Apart from use of inappropriate drug dosages in patients with impaired renal or hepatic function, presence of well-defined anticancer drug-specific risk factors such as DPD deficiency in case of FU-based chemotherapy (Diasio et al, 1988(Diasio et al, , 1998Johnson et al, 1999;Milano et al, 1999), and to some extend gender (Stein et al, 1995;Sloan et al, 2002) and age 465 (Stein et al, 1995;Cascinu et al, 1996;Chiara et al, 1998;Popescu et al, 1999), the reason/mechanism is still unclear which predisposes patients to experience chemotherapy-related side effects.…”
mentioning
confidence: 99%
“…Previous retrospective studies evaluating 5-FU þ leucovorin regimens in an elderly population reported severe toxicity in 20% of patients treated with the LV5FU2 regimen (Mabro et al, 1999) and in 58% of patients One patient was treated with an association of raltitrexed and oxaliplatin, two patients with an association of capecitabine and oxaliplatin and one patient with an association of raltitrexed and irinotecan. Oxaliplatin or irinotecan chemotherapy in the elderly T Aparicio et al treated with the 5-FU bolus regimen (Stein et al, 1995). We report severe neutropenia in 14 and 23% of patients treated with oxaliplatin and irinotecan, respectively.…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, patients over 75 years have been usually excluded from randomised clinical trials evaluating chemotherapy for advanced colorectal cancer (Trimble et al, 1994;Kohne et al, 2001). Few data are available on chemotherapy in elderly patients, but it has been suggested that 5-fluorouracil (5-FU)-based chemotherapy efficacy was comparable to that in younger patients (Stein et al, 1995;Chiara et al, 1998;Mabro et al, 1999;Popescu et al, 1999;Magne et al, 2002). Tolerance was comparable except in one study evaluating chemotherapy with bolus 5-FU (Stein et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation